Decrease in Shiga toxin expression using a minimal inhibitory concentration of rifampicin followed by bactericidal gentamicin treatment enhances survival of Escherichia coli O157:H7-infected BALB/c mice - Abdelnoor Alexander M; Sabra Ahmad; Kazzi Natalie; Rahal Elias A; Matar Ghassan M (BMC, 2011)
Abstract Background Treatment of Escherichia coli O157:H7 infections with antimicrobial agents is controversial due to an association with potentially fatal sequelae. The production of Shiga toxins is believed to be central to the pathogenesis of this organism. Therefore, decreasing the expression of these toxins prior to bacterial eradication may provide a safer course of therapy. Methods The utility of decreasing Shiga toxin gene expression in E. coli O157:H7 with rifampicin prior to bacterial eradication with gentamicin was evaluated in vitro using real-time reverse-transcription polymerase chain reaction. Toxin release from treated bacterial cells was assayed for with reverse passive latex agglutination. The effect of this treatment on the survival of E. coli O157:H7-infected BALB/c mice was also monitored. Results Transcription of Shiga toxin-encoding genes was considerably decreased as an effect of treating E. coli O157:H7 in vitro with the minimum inhibitory concentration (MIC) of rifampicin followed by the minimum bactericidal concentration (MBC) of gentamicin (> 99% decrease) compared to treatment with gentamicin alone (50-75% decrease). The release of Shiga toxins from E. coli O157:H7 incubated with the MIC of rifampicin followed by addition of the MBC of gentamicin was decreased as well. On the other hand, the highest survival rate in BALB/c mice infected with E. coli O157:H7 was observed in those treated with the in vivo MIC equivalent dose of rifampicin followed by the in vivo MBC equivalent dose of gentamicin compared to mice treated with gentamicin or rifampicin alone. Conclusions The use of non-lethal expression-inhibitory doses of antimicrobial agents prior to bactericidal ones in treating E. coli O157:H7 infection is effective and may be potentially useful in human infections with this agent in addition to other Shiga toxin producing E. coli strains.